La provisión de medios de pago y su control - W. T. Newlyn (Económica, 1966)
To examine seriatim following propositions, of the "new orthodoxy" of the supply of mediums of exchange: 1. The supply of Treasury Bills is the effective regulatory base of the domestic banking system; 2. Capability of open market operations to influencing the volume of bank deposits; 3. Uniquely of the assets or group of assets compared to money; 4. Possibility to put liquid assets in the place of money; 5. The basis for believing that there is any limit to velocity. He concludes without violation of the traditional analysis, it to say, that: 1. The cash continues being the base of the banking system, because the supply of Treasury Bills is neither a necessary and sufficient condition for a change in deposits; 2. There is no structural reason why open-market operations should be ineffective; 3. Assets can be uniquely identified as money (medium of exchange) if the aggregate of the class of assets to which they belong remains the same and there is no repercussion in the market for loans; 4. a) In analysis of the effects of asset choice, liquidity (in the maturity sense) must be put in the place of money as the monetary factor influencing effective demand by the rate of interest and valuation effects; b) In analysis of the determinants of expenditure plans, the liquidity (in the financial strength sense) must be put in the place, of money as the factor influencing directly; c) In analysis of the effect of expending decisions the availability of money be retained as a factor capable of influencing the ex-post realisations of such decision because of its unique position as the medium of exchange; 5. a) When the volume of money is large, monetary restriction is ineffective because velocity of circulation can increase without constraint; b) The development ex non-bank financial intermediaries causes a secular increase in the velocity of circulation, but the credit which they create is based upon money.